Antibacterial activity of ethanolic extract of leaves and bulbs of Crinum asiaticum L. against acne-inducing bacteria - Azrifitria .; Syaikhul Aziz; Chairul . (Indonesian Journal of Pharmacy, 2010)
The antibacterial activity of ethanolic extract of leaves and bulbs of Crinum asiaticum L. was tested against Propionibacterium acnes, Staphylococcus aureus and  Staphylococcus epidermidis, pathogenic bacteria that cause acne. Minimum Inhibitory  Concentration  (MIC)  and  Minimum  Bactericidal  Concentration  (MBC) were  determined  by  dilution  methods.  MIC  and  MBC  of  ethanol  leaves  extract were  found  for  P.  acnes  (1.25  and  2.5  mg/mL),  S.  aureus  (5  and  10  mg/mL) and  S.  epidermidis  (2.5  and  5  mg/mL).  While  MIC  and  MBC  of  ethanol  bulbs extract  were  found  for  P.  acnes  (7.5  and  15  mg/mL),  S.  aureus  (7.5  and 15 mg/mL) and  S. epidermidis  (3.75 and 7.5 mg/mL). Further study conducted on  the  ethanol  leaves  extract  against  P.  acnes  to  analyze  cell  leakage  (nucleic acid  and  protein)  by  ultraviolet  spectrophotometry,  metal  ion  (K+ and  Ca2+)  by atomic  absorption  spectrometry,  and  observed  alteration  of  the  cell  wall  by scanning  electron  microscopy  (SEM).  The  result  showed  that  ethanol  leaves extract could damage the cell wall and affect the permeability of cell membrane which  marked  by  release  of  nucleic  acid  (absorbance  0.3307-0.4299),  protein (absorbance  0.0616-0.101),  ion  K+ (8.167-15.757  mg/mL),  ion  Ca2+ (5.47-13.74 mg/L) from the cell and alter morphology of cell wall of P. acnes.Key words: Antibacterial, Crinum asiaticum L., Propionibacterium acnes